PENGUATAN MATERI MENULIS TEKS PIDATO PERSUASIF MATA PELAJARAN BAHASA INDONESIA KELAS IX SMP NEGERI 2 BALIKPAPAN SELATAN - Ari Musdolifah; Nurliani Maulida (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Activities "Strengthening Material Writing Persuasive Speech Texts Subjects Indonesian Class IX State Junior High School 2 South Balikpapan" is a Community Service (PKM) activity as an effort to motivate children to be skilled in writing persuasive speech texts. The activity is based on the weak understanding of learners related to the rules of language when writing persuasive speech texts. This activity is carried out with four stages, namely preparation, implementation, evaluation, and preparation of reports. This activity is carried out by carrying out learning through the Zoom Meeting application by providing persuasive speech text material, namely definitions, examples, structures, and proverbs. The implementer of this activity is a lecturer of the Faculty of Teacher Training and Education (FKIP) as a speaker and subject teacher Indonesian grades IX-1, 2, and 3 as moderators. With this activity, it is expected to motivate children to be skilled in writing persuasive speech texts.